Therapeutic Phytochemical Actives for Potential Control of SARS-CoV-2 - Dey, Dipjyoti; Dey, Nirban; Ghosh, Shalini; Khan, Imran; Thiagarajan, Padma (Indian Journal of Pharmaceutical Education and Research, 2021)
Background: Drug development strategies for treating COVID-19 focus on actives that either physically block angiotensin-converting enzyme-2 (ACE-2) receptors (viral entry point), or those, which inactivate viral proteases like 3CLpro or RdRp, inside the infected host cells. Objectives: The objective of the present study is to virtually screen phytochemicals for both these purposes. Methods: Molecular docking, molecular dynamic simulation (MDS) and multiple sequence alignment were employed. Results: All the screened phytochemical actives showed negative binding energies with their respective targets, attesting good complex stabilities. Among each set of ten actives, for blocking ACE-2 receptors and for inactivation of 3CLpro and RdRp, Dichamanetin- ACE-2, Glabrene-3CLpro and Naringenin-RdRp complexes were most stable, with binding energies of -9.8, -9.11 and -7.7 Kcal/mol respectively. MDS studies of these representative actives and their complexes, also attested to complex stabilities. Multiple sequence alignment analysis of nine significant amino acid residues of the Homo sapiens ACE-2 receptor, with nine different species, showed conservation of several residues. Conclusion: A set of phytochemicals actives can block ACE-2 receptors and prevent the entry of SARS-CoV-2 into host endothelial cells. Two other sets of actives can inactivate viral 3CLpro and RdRp enzymes and prevent replication of SARS-CoV-2 inside host cells. They all can hence be further explored for the control of COVID-19.
Keywords: COVID-19; SARS-CoV-2; Angiotensin Converting Enzyme-2; 3CLpro; RdRp